2011
DOI: 10.1021/jf202887c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Isothiocyanate Metabolite Levels and Histone Deacetylase Activity in Human Subjects Consuming Broccoli Sprouts or Broccoli Supplement

Abstract: Increased consumption of cruciferous vegetables such as broccoli may reduce the risk of various cancers. Myrosinase is required to convert dietary glucosinolates from broccoli into bioactive isothiocyanates. We evaluated isothiocyanate excretion profiles in healthy subjects who consumed broccoli sprouts or broccoli supplement (no myrosinase) with equivalent glucosinolate content. Urinary metabolites of two major isothiocyanates, sulforaphane and erucin, were measured by liquid chromatography coupled with tande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 31 publications
(78 reference statements)
5
65
0
1
Order By: Relevance
“…In humans, the bioavailability of supplemental free sulforaphane is about fourfold greater than the bioavailability of sulforaphane originating as part of glucoraphanin [17]. Others have observed 7-to 12-fold increases in sulforaphane absorption when broccoli products or glucoraphanin are ingested in the presence of myrosinase activity [18][19][20][21][22]. All of these data confirm the importance of myrosinase activity for human absorption of sulforaphane from broccoli and broccoli products [6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 72%
“…In humans, the bioavailability of supplemental free sulforaphane is about fourfold greater than the bioavailability of sulforaphane originating as part of glucoraphanin [17]. Others have observed 7-to 12-fold increases in sulforaphane absorption when broccoli products or glucoraphanin are ingested in the presence of myrosinase activity [18][19][20][21][22]. All of these data confirm the importance of myrosinase activity for human absorption of sulforaphane from broccoli and broccoli products [6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 72%
“…Brassica oleracea juice was administered to rats based on animal weight (340 ml/120 mg), as calculated on the basis of amounts of broccoli sprouts administered to humans in the previous studies [18,19]. GW6471 was first solved in dimethyl sulfoxide and then further diluted in 0.9% NaCl solution to reach the final concentration.…”
Section: Total Polyphenols Flavonoids and Anthocyaninsmentioning
confidence: 99%
“…Anticancer effects of SFN has been proven in numerous cancer cell lines and in vivo experiments (18). Mechanisms of SFN action are complex and include inhibition of phase I xenobiotic metabolizing enzymes, induction of phase II detoxification enzymes, inhibition of histone deacetylases, induction of oxidative stress, genotoxic stress, inhibition of microtubule dynamics, and modulation of numerous signaling pathways leading to cell cycle arrest and apoptosis of cancer cells (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Recently, it has been shown that SFN inhibits Akt-mTOR-S6K prosurvival pathway, which results in global protein synthesis inhibition and decreased survival of phenotypically different breast cancer cells (31).…”
Section: Introductionmentioning
confidence: 99%